2005
DOI: 10.1038/sj.ejcn.1602229
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cholesterol and triglyceride concentrations in the Vanguard population of the Carotene and Retinol Efficacy Trial (CARET)

Abstract: Background: The Beta-Carotene and Retinol Efficacy Trial (CARET) was terminated 21 months ahead of schedule due to an excess of lung cancers. Deaths from cardiovascular disease also increased (relative risk ¼ 1.26 (95% confidence interval (CI) 0.99-1.61)) in the group assigned to a combination of 30 mg beta-carotene and 25 000 IU retinyl palmitate (vitamin A) daily. The basis for increased cardiovascular mortality is unexplained. Design: We analyzed data on serum lipids, available for 1474 CARET Vanguard parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Interestingly, our data shows no effect of fenretinide on fibrinogen and triglyceride levels differently from other retinoids [45], but is consistent with our previous results [46,47]. The observed association between fenretinide administration and the reduction trend of AT-III is new and requires further investigation to assess its potential clinical impact.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, our data shows no effect of fenretinide on fibrinogen and triglyceride levels differently from other retinoids [45], but is consistent with our previous results [46,47]. The observed association between fenretinide administration and the reduction trend of AT-III is new and requires further investigation to assess its potential clinical impact.…”
Section: Discussionsupporting
confidence: 92%
“…In order to explain the increased cardiovascular mortality observed in the Carotene and Retinol Efficacy Trial (CARET), Cartmel et al suggested a possible contribution of hypercholesterolemia and hypertriglyceridemia in the treatment arm compared to placebo [45]. On the contrary, fenretinide has a neutral effect on tests of liver function, lipid profile and blood cell counts as compared to other retinoids [46].…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the Vanguard phase, the Data Safety and Monitoring Board will inform the National Institutes of Health about the advisability of continuing one or both trials. Employed successfully in other trials, 36,37 this phased approach combining pilot and efficacy components into a single study allows subjects enrolled in the feasibility phase to be included in the final analysis of primary and secondary outcomes.…”
Section: Specific Methodological Issues Vanguard Designmentioning
confidence: 98%
“…Despite the lack of a consistent explanation for this result, serum beta-carotene is transported in lipoproteins, mainly in LDL-c. Beta-carotene concentrations less than 0.25 mmol/L have been associated with an increased risk of coronary atherosclerotic disease progression in HIV-infected patients (30); the most likely mechanism seems to be reduced oxidation of LDL-c.…”
Section: Discussionmentioning
confidence: 99%